(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In an attempt to classifiy potatoes based on features of gray level co-occurrence matrix properties using support vector machine classifier in to five classes.Potato images are captured using developed setup. The developed image capturing setup has a resolution of 0.22 mm per pixel. The four parameters of gray level co-occurrence matrix such as variance, correlation, uniformity and homogeneity are calculated from each image and the data set has been prepared